Child, parent or family? Applying a systemic lens to the conceptualisations of Family Support in Europe. Issue 2 (4th March 2023) - Devaney, Carmel; Christiansen, Øivin; Holzer, Julia; MacDonald, Mandi; Matias, Marisa; Salamon, Eszter
ABSTRACT: This paper considers how Family Support is conceptualised in the European context with respect to its primary beneficiaries. The central question considers the focus of concern in a child welfare system and what it means when Family Support is focused on children, on parents, or involves the family unit as a whole. Informed by a body of relevant literature reviewed as part of a wider project, Family Support is seen as more often conceptualised as being targeted toward parents as the primary service user, and to a lesser extent described as being tailored toward children or whole families. This approach to Family Support provision is somewhat at odds with a systemic understanding of families, which is foundational to much social care and child welfare work, and which takes account of the multi-layered relationships between individuals within families, and between individuals, families and their social world. Applying an ecological systems perspective, this paper critically discusses the consequences for the involved stakeholders and the implementation of services at different system levels when support and interventions are targeted at the child, the parents or at the family as a whole.